Nursing Students' Intercultural Learning via Internationalization at Home: A Qualitative Descriptive Study. (May 2017) - Chan, E. Angela; Lai, Timothy; Wong, Arkers; Ho, Suki; Chan, Bessie; Stenberg, Marie; Carlson, Elisabeth
Highlights: A shift from factual to experiential knowledge for better intercultural interaction. Reflection and relaxed attitude facilitated interactive intercultural learning. Intercultural reflective learning was related to desirable nursing qualities. Skype provided visual cues are beneficial to intercultural learning.